Evidence for negative association of the chemokine receptor CCR5 d32 polymorphism with rheumatoid arthritis. Issue 3 (26th August 2004) - Pokorny, V; McQueen, F; Yeoman, S; Merriman, M; Merriman, A; Harrison, A; Highton, J; McLean, L
Abstract : Background: Ligands of chemokine receptor CCR5, including MIP-1α, MIP-1β, and RANTES, have been implicated in rheumatoid arthritis. Objective: To test whether CCR5 d32 polymorphism has a negative association with rheumatoid arthritis in a New Zealand cohort. Methods: 516 white patients with rheumatoid arthritis and 985 healthy controls were investigated by PCR amplification of the region flanking the known CCR5 d32 deletion, and the frequencies of CCR5 d32 compared. An early rheumatoid arthritis (ERA) cohort of 92 patients was followed prospectively for two years; disease severity and outcome were correlated with CCR5 d32 status. Results: 12 control subjects (1.2%) were homozygous for d32; no d32 homozygous rheumatoid patients were detected (p = 0.012); 56 patients (10.9%) were heterozygous for the d32 polymorphism (d32/wt), compared with 169 controls (17.2%) (p = 0.0011). The CCR5 d32 allele frequency was lower in the rheumatoid patients than in the controls (frequencies of 0.054 and 0.098, respectively; p = 3.7×10 −5 ). The frequency of CCR5 d32 did not differ significantly according to disease severity or outcome in the prospective ERA cohort, nor with HLA-DRB1 status. Conclusions: This study provides further evidence for a protective effect of the CCR5 d32 variant on rheumatoid arthritis, consistent with a role for CCR5 and its ligands in disease pathogenesis.